An Introduction to the Views of Traditionalists on Islamic Art and Architecture through the Critique of Titus Burckhardt - Shohreh Javadi (هنر و تمدن شرق)
Most traditionalist thinkers, influenced by Sufi Islam and emphasizing the mystical aspects, believe in a shared and universal supernatural truth inherent in religious traditions. This intellectual movement, initiated by René Guénon and carried forward by figures such as Titus Burckhardt, Frithjof Schuon, Ananda Coomaraswamy, and Martin Lings, has significantly influenced contemporary comparative theology. Within the Islamic world, it intertwines with mystical currents and Eastern religious practices. These theorists express their views through Islamic architecture and art, employing illogical and emotional arguments that have led to confusion and disorder in Iran’s cultural and artistic community for many years. Critiquing Burckhardt’s views on the theoretical foundations of art and the manifestations of Islamic art and architecture reveals a tendency towards sanctification and a retreat from rationality, aiming to offer a realistic and logical assessment of the arts in the Islamic world. Traditionalists, emphasizing perennial wisdom, hold a belief in a fixed, sacred, and esoteric tradition across all human religions, perceiving a common tradition in Islam, Christianity, Judaism, and Eastern Asian religions. Unfortunately, their definition of tradition diverges significantly from the Islamic understanding found in the Holy Quran, leading to gross misinterpretations and unscientific interpretations in various fields, particularly in Islamic art and architecture.